Hsa-miR-379 down-regulates Rac1/MLK3/JNK/AP-1/Collagen I cascade reaction by targeting connective tissue growth factor in human alveolar basal epithelial A549 cells. (June 2023) - Shan, Jing; Wu, Meng-Yu; Zhang, Ying-Chi; Lin, Yu-Jia; Cheng, Bin; Gao, Yan-Rong; Liu, Zhi-Hong; Xu, Hai-Ming
Graphical abstract: Highlights: Hsa-miR-379-3p could directly target and down-regulate human CTGF gene. The overexpression of hsa-miR-379-3p could down-regulate the expression level of CTGF. The overexpression of hsa-miR-379-3p could further reduce the expression levels of key genes and proteins in CTGF mediated Rac1/MLK3/JNK/AP-1/Collagen I cascade reaction. Abstract: Objective: This study was aimed to screen and identify miRNAs that could regulate human CTGF gene and downstream cascade reaction Rac1/MLK3/JNK/AP-1/Collagen I by bioinformatics and experimental means. Methods: TargetScan and Tarbase were used to predict miRNAs that may have regulatory effects on human CTGF gene. The dual-luciferase reporter gene assay was employed to verify the results obtained in bioinformatics. Human alveolar basal epithelial A549 cells were exposed to silica (SiO2 ) culture medium for 24 h to establish an in vitro model of pulmonary fibrosis, and bleomycin (BLM) of 100 ng/mL was used as a positive control. The miRNA and mRNA expression levels were determined by RT-qPCR, and the protein levels were measured by western blot in hsa-miR-379-3p overexpression group or not. Results: A total of 9 differentially expressed miRNAs that might regulate the human CTGF gene were predicted. Hsa-miR-379-3p and hsa-miR-411-3p were selected for the subsequent experiments. The results of the dual-luciferase reporter assay showed that hsa-miR-379-3p could bind to CTGF, but hsa-miR-411-3p could not. Compared with the control group, SiO2 exposure (25 and 50 μg/mL) could significantly reduce the expression level of hsa-miR-379-3p in A549 cells. SiO2 exposure (50 μg/mL) could significantly increase the mRNA expression levels of CTGF, Collagen I, Rac1, MLK3, JNK, AP1, and VIM in A549 cells, while CDH1 level was significantly decreased. Compared with SiO2 + NC group, the mRNA expression levels of CTGF, Collagen I, Rac1, MLK3, JNK, AP1, and VIM were significantly decreased, and CDH1 level was significantly higher when hsa-miR-379-3p was overexpressed. At the same time, overexpression of hsa-miR-379-3p improved the protein levels of CTGF, Collagen I, c-Jun and phospho-c-Jun, JNK1 and phospho-JNK1 significantly compared with SiO2 + NC group. Conclusion: Hsa-miR-379-3p was demonstrated for the first time that could directly target and down-regulate human CTGF gene, and further affect the expression levels of key genes and proteins in Rac1/MLK3/JNK/AP-1/Collagen I cascade reaction.